Natural resistance of tomato plants to Tomato yellow leaf curl virus - H. El-Sappah, Ahmed; Qi, Shiming; A. Soaud, Salma; Huang, Qiulan; M. Saleh, Alaa; A. S. Abourehab, Mohammed; Wan, Lingyun; Cheng, Guo-ting; Liu, Jingyi; Ihtisham, Muhammad; Noor, Zarqa; Rouf Mir, Reyazul; et al. (Frontiers in Plant Science, 2022)
TYLCV is one of the most harmful afflictions in the world that affects tomato (Solanum lycopersicum) growth and production. Six regular antagonistic genes (Ty-1, Ty-2, Ty-3, Ty-4, ty-5, and Ty-6) have been transferred from wild germplasms to commercial cultivars as TYLCV protections. With Ty-1 serving as an appropriate source of TYLCV resistance, only Ty-1, Ty-2, and Ty-3 displayed substantial levels of opposition in a few strains. It has been possible to clone three TYLCV opposition genes (Ty-1/Ty-3, Ty-2, and ty-5) that target three antiviral safety mechanisms. However, it significantly impacts obtaining permanent resistance to TYLCV, trying to maintain opposition whenever possible, and spreading opposition globally. Utilizing novel methods, such as using resistance genes and identifying new resistance resources, protects against TYLCV in tomato production. To facilitate the breeders make an informed decision and testing methods for TYLCV blockage, this study highlights the portrayal of typical obstruction genes, common opposition sources, and subatomic indicators. The main goal is to provide a fictitious starting point for the identification and application of resistance genes as well as the maturation of tomato varieties that are TYLCV-resistant.